2017
DOI: 10.31899/pgy8.1034
|View full text |Cite
|
Sign up to set email alerts
|

The global state of evidence on interventions to prevent child marriage

Abstract: * Countries that set age 18 as the legal minimum age of marriage but permit exceptions under the law (e.g., with parental or judicial consent) were not considered to have laws banning child marriage. Since the publication of these data, five countries (Bangladesh, Gambia, Kenya, Malawi, Tanzania) have passed legislation modifying their legal minimum age of marriage. The current statistic reflects these recent changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 12 publications
1
36
0
3
Order By: Relevance
“…El M/UIF se reconoce como un problema en todo el mundo debido a sus efectos adversos en el acceso de las niñas a sus derechos y bienestar, ya que marca el final de su niñez, forzándolas a desempeñar actividades para las que no están física ni emocionalmente preparadas. 2 Casarse antes de los 18 años se asocia con un aumento de la fecundidad y el crecimiento de la población, porque el matrimonio temprano alarga el tiempo que las niñas y las mujeres permanecen en la edad fértil y acorta el lapso entre generaciones 6 . Esta práctica también socava la capacidad de una niña para acceder a la educación que permita desarrollar su autonomía y la expone a las consecuencias peligrosas del parto antes de la madurez física 17 .…”
Section: Antecedentesunclassified
“…El M/UIF se reconoce como un problema en todo el mundo debido a sus efectos adversos en el acceso de las niñas a sus derechos y bienestar, ya que marca el final de su niñez, forzándolas a desempeñar actividades para las que no están física ni emocionalmente preparadas. 2 Casarse antes de los 18 años se asocia con un aumento de la fecundidad y el crecimiento de la población, porque el matrimonio temprano alarga el tiempo que las niñas y las mujeres permanecen en la edad fértil y acorta el lapso entre generaciones 6 . Esta práctica también socava la capacidad de una niña para acceder a la educación que permita desarrollar su autonomía y la expone a las consecuencias peligrosas del parto antes de la madurez física 17 .…”
Section: Antecedentesunclassified
“…An interesting effect of the legal prohibition is documented in the modification of the treatment provided by midwives and other health providers to pregnant girls and adolescents, who now prefer to refer them to the official health system because of the legal implications of caring for minors. Three patterns associated with the marriage process were identified: (1) In the past, parents arranged the daughters' marriages without their opinion; (2) In the present, parents arrange marriages or unions to resolve economic issues or to conceal a pregnancy; and (3) marriages or unions are decided by the girls. In the general discourse adolescents are held responsible for being the ones who maintain an interest in early unions in order to reach better spaces of emotional coexistence and economic well-being.…”
Section: Executive Summarymentioning
confidence: 99%
“…31 CEFM/U is recognized as a problem throughout the world due to its adverse effects on girls' access to their rights and well-being, as it marks the end of their childhood, forcing them to perform activities for which they are not physically or emotionally prepared. 2 Marriage before the age of 18 is associated with an increase in fertility and population growth, because early marriage lengthens the time that girls and women remain in the fertile age and shortens the time between generations. 6 This practice also undermines a girl's ability to access education that allows her to develop her autonomy and exposes her to the dangerous consequences of childbirth before physical maturity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous reviews, this review found economic approaches such as conditional cash/asset transfers to be of limited effectiveness. 8 Given the sheer numbers of girls at risk of child marriage globally, the challenge to accelerate elimination of the practice is daunting. Pilot programs to prevent or reduce child marriage, whether evaluated or not, typically overlook the costs and scalability of the intervention design.…”
Section: Introductionmentioning
confidence: 99%